Education based market projection and demands - Siti Maisarah, Ibrahim (2023)
In order to introduce the education programme to undergraduates, learning content is crucial to ensure the content and skills are aligned with the market projection. The objectives of this study are to identify, analyse and determine the types of educational programmes may be offered given the economic outlook for Malaysia and the rest of the world, utilising any useful projection and prediction techniques. The graphical representative and methods used to analyse the types of education based on market demand in this study are data visualization, correlation analysis and Artificial Neural Network. Data that used in this study is a data from a git repo that contains data from what was originally the American Community Survey 2010-2012 Public Use Microdata Series which is retrieved from Kaggle. One of the outputs of the study is the interactive dashboards with helpful data that the university can utilise to share with others. It is can be concluded that major in engineering has the highest number of students that require college degree because of the industry demand. The use of correlation analysis to determine the relationship between economic scenarios and sustainable educational initiatives. It is clear from the scatter plot analysis that several education programmes, including those in agriculture and natural resources, biology and life science, computers and mathematics, education, and industrial arts and consumer services, have the lowest unemployment rates. The future unemployment rates based on the 16 main categories in the dataset were examined according to projection and prediction using ANN. Six of these groups demonstrated a decline in unemployment, while 10 indicated an increase. Biology and biological sciences, physical sciences, engineering, and psychology and social work all exhibited a declining trend in unemployment rates among the key categories examined. This study assists and direct the student in selecting the academic courses and a set of skills that correspond to market demands. The results of this study assist universities in reskilling existing courses or developing novel programmes to address the newly discovered skills.